Ugandan Women on the Move to Stay Connected: The Concurrency of Fixation and Liberation - Mogensen, Hanne O. (Anthropologica, 2022)
Many Ugandan women are constantly moving around as part of their everyday efforts to make life continue. Based on fieldwork in southeastern Uganda in the past 15 years, exam- ples are given of how women moving between relatives and tem- porary jobs obtain continuity in their lives while also attempt- ing to break with previous relationships and contexts to embrace new situations and possibilities. It is suggested that we need to approach connection and disjunction, fixation and liberation as concurrent principles in the ongoing struggle for their own and their children’s survival, in order to catch sight of the different kinds of networks and relationships that are at stake in peo- ple’s lives.